2021
DOI: 10.21037/tau-21-81
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the lncRNA-miRNA-mRNA regulatory network for bladder cancer

Abstract: Background: Long non-coding RNAs (lncRNAs) are essential regulators for various human cancers.However, these lncRNAs need to be further classified for cancer. In the present study, we identified novel competing endogenous RNA (ceRNA) network for bladder cancer (BC) and explored the gene functions of the ceRNA regulatory network.Methods: Differential gene expression analysis were performed on The Cancer Genome Atlas Urothelial Bladder Carcinoma (TCGA-BLCA) datasets to identify differentially expressed messenger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…Utilizing the TCGA database, this study detected higher SERPINE2 mRNA expression in UBUC, which has been associated with poor survival. The abovementioned finding is consistent with those of a study by Huang et al [31]. Recently, Lin et al [32] also identified that SERPINE2 could predict OS in patients with UBUC based on five cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…Utilizing the TCGA database, this study detected higher SERPINE2 mRNA expression in UBUC, which has been associated with poor survival. The abovementioned finding is consistent with those of a study by Huang et al [31]. Recently, Lin et al [32] also identified that SERPINE2 could predict OS in patients with UBUC based on five cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…Yang et al (32) indicated that SPTBN2 was a potential driver gene in breast cancer and endometrial cancer. Huang et al (33) identified the significant upregulation of SPTBN2 expression in bladder cancer tumor samples compared with normal samples, and SPTBN2 expression was associated with a poor prognosis in bladder cancer. Zhang et al (34) discovered that the expression of SPTBN2 was significantly upregulated in colorectal cancer patients with distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the lncRNA/miRNA/mRNA network in various biological progression has been elucidated in recent decades. As a major cause of cancer initiation and progression, multiple gene mutations have drawn wide scientific interests, and considerable effort has been exerted to elucidate the molecular mechanisms that contribute to tumorigenesis via the lncRNA/miRNA/mRNA network, such as bladder cancer, hepatocellular carcinoma, osteosarcoma, gastric cancer, oral cancer, and CC [ 21 26 ]. lncRNA-CTS regulates CC progression via the miR-505/ZEB2 axis [ 27 ], lncRNA TP73-AS1 modulates CC development via the miR-329-3p/ARF1 axis [ 28 ], lncRNA CAR10 promotes CC progression via the miR-125b-5p/PDPK1 pathway [ 29 ], and lncRNA DANCR aggravates CC development via the miR-335-5p/ROCK1 axis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%